Fundamental movement patterns and potential risk of injuries in 1st and 2nd division Polish handball players - Slodownik, R.; Ogonowska-Slodownik, A.; Morgulec-Adamowicz, N.; Targosinski, P. (Trends in Sport Sciences, 2014)
The Functional Movement Screen™ (FMS™) is one of modern functional assessment tools used, for example, for qualitative evaluation of fundamental movement patterns and potential injury risks. Aim of Study: The purpose of this study was to assess the performance of handball players with the use of Functional Movement Screen™ (FMS™) in consideration of their competitive level, position on the court and symmetry of movement patterns. Material and Methods. Thirty 1st and 2nd division handball players participated in the study. All subjects were healthy men aged 23.23 ± 3.59 years, with body height of 184 ± 5.6 cm and body mass of 86.37 ± 8.61 kg. The players performed seven tests from the Functional Movement Screen™. Statistical analysis was made using the SPSS Statistics 21.0 software package. The level of statistical significance was set at p = 0.05. Results: No significant differences in handball players` general characteristics were found between both divisions. Student`s t-test showed no significant differences between the two groups in total FMS™ score. Statistically significant differences were noted in the Shoulder Mobility (SM) test (U = 308.5; p = 0.014) between the right and the left upper extremity. Conclusions: The study revealed no statistically significant differences in FMS™ test scores between the 1st and 2nd division handball players as well as between players in different playing positions on the court. Also no higher risk of injury was shown among the 1st and 2nd division handball players. The study confirmed, however, characteristic adaptation of the throwing arm typical for throwing sports in the form of glenohumeral internal rotation deficit.